A scheduling perspective on the monetary value of improving process control. (6th April 2018) - Costandy, Joseph G.; Edgar, Thomas F.; Baldea, Michael
Highlights: We delineate the influence of control on optimal production scheduling problems. We examine the use of total or individual transition times as value metrics. We demonstrate that both metrics are suitable for economic benefit analysis for process control. We illustrate the role of closed-loop system nonlinearity on the value of improving control. Abstract: The goal of quantifying the monetary value of process control has been a target of much research since the inception of the field, and methods have been developed for quantifying the value of control in the case of predominantly steady-state processes. However, there has been no attempt to quantify the monetary value of control for predominantly transient processes. In this work, we utilize the general framework of integrated scheduling and control to develop novel performance functions that enable the quantification of the monetary value of control from a scheduling perspective for a predominantly transient process. Specifically, we posit that the transition time between one product and the next in a production sequence can be used as a performance metric over which the value of control can be quantified. We demonstrate the utility of the developed performance functions using a case study of the scheduling of a multi-product CSTR.